Status Karies Gigi Berdasarkan Indeks DMF-T pada Nelayan di Pesisir Pantai Kawasan Megamas Kota Manado - Ni Wayan Mariati; Christy N. Mintjelungan; Nur I. Martin (Universitas Sam Ratulangi, 2024)
Abstract: Most fishermen in Indonesia are under the poverty line and have a low level of education, which can affect the level of dental and oral hygiene. The most common dental and oral disease found in coastal communities is dental caries. The main indicator for assessing dental caries is the DMF-T index (Decay Missing Filling-Teeth). This study aimed to determine the status of dental caries based on the DMF-T index in fishermen in the coastal area of the Megamas region, Manado. This was a descriptive study with a cross sectional design. Samples were fishermen on the coastal area of the Megamas region obtained by using total sampling method according to the inclusion criteria. There were 34 fishermen in this study. The results showed that the status of dental caries based on DMF-T was 104 (30%) Decay with an average of 3.1; Missing was 243 (70%) with an average of 7.1; and Filling was 0 (0%) or none. The total DMF-T index was 347 with an average of 10.2. In conclusion, the status of dental caries based on the DMF-T index in fishermen in the coastal area of the Megamas Region, Manado, is very high with an average value of 10.2. Keywords: dental caries status; DMF-T index; oral and dental hygiene; fishermen Abstrak: Sebagian besar nelayan di Indonesia berada di bawah garis kemiskinan serta tingkat pendidikan rendah yang dapat memengaruhi tingkat kebersihan gigi dan mulut. Penyakit gigi dan mulut yang paling sering ditemukan pada masyarakat pesisir Pantai yaitu karies gigi. Indikator utama untuk menilai karies gigi yaitu indeks DMF-T (Decay Missing Filling-Teeth). Penelitian ini bertujuan untuk mengetahui status karies gigi berdasarkan indeks DMF-T pada nelayan di pesisir pantai Kawasan Megamas Kota Manado. Jenis penelitian ialah deskriptif dengan desain potong lintang. Sampel penelitian yaitu nelayan di pesisir pantai Kawasan Megamas Kota Manado, diperoleh dengan metode total sampling yang sesuai dengan kriteria inklusi. Hasil penelitian mendapatkan 34 nelayan sebagai sampel penelitian. Status karies gigi berdasarkan DMF-T yaitu Decay sebanyak 104 (30%) dengan rerata 3,1, Missing sebanyak 243 (70%) dengan rerata 7,1 dan Filling sebanyak 0 (0%) atau tidak ada. Total indeks DMF-T sebesar 347 dengan rerata 10,2. Simpulan penelitian ini ialah status karies gigi berdasarkan indeks DMF-T pada nelayan di pesisir pantai Kawasan Megamas Kota Manado termasuk kriteria sangat tinggi dengan nilai rerata 10,2. Kata kunci: status karies gigi; indeks DMF-T; kebersihan gigi dan mulut; nelayan